Pteropine Orthoreovirus, PRV7S (Sikamat Virus) Demonstrates Oncolysis in Nasopharyngeal Carcinoma Cell Lines - Alson Loh; Nur Adania Shaibie; Po Qhuan Chan; Pooi Pooi Leong; Sharrada Segeran; Boon Keat Tan; Siew Tung Wong; Rhun Yian Koh; Soi Moi Chye; Kenny Voon (Frontiers in Bioscience-Landmark, 2022)
Background: Oncolytic properties had been demonstrated in Mammalian Orthoreovirus (MRV) and Avian Orthorevirus (ARV). Besides MRV and ARV, Pteropine Orthoreovirus (PRV) is also categorized under the genus Orthoreovirus. PRV7S (Sikamat virus) is an orthoreovirus isolated in Malaysia. Present study aims to investigate the oncolytic effects of PRV7S on ranges of nasopharyngeal carcinoma (NPC) cells through apoptosis in comparison to MRV3. Methods: Non-cancerous nasopharyngeal (NCNP) and NPC cells were infected by PRV7S and MRV3. The effects of PRV7S on the proliferation inhibition and apoptotic activity of NPC cells was examined using MTT assay and flow cytometry. Additionally, western blot assay was performed to analyze the expression of RAS and apoptotic protein. Lastly, qPCR assay was performed to demonstrate that PRV7S and MRV3 replicated in infected-NPC and infected-NCNP cells. Results: The proliferation of NPC cells were significantly inhibited after PRV7S infection in a time dependent manner in comparison to infected-NCPC cells. Flow cytometry analysis showed that PRV7S infection was able to induce apoptosis on NPC cells at 48 hpi. Western blot results showed that upon PRV7S infection, N/H/K RAS protein expression was reduced, whereas caspase-3 protein expression increased in NPC cells. qPCR assay showed higher viral load of PRV7S found in infected-NPC compared to infected-NCNP cells. Conclusions: PRV7S inhibits the proliferation and induces apoptosis of NPC cells similar to MRV3. Therefore, PRV7S is a potential oncolytic virus.